Avaliação das propriedades térmicas de concretos com ar incorporado - Cintra, Laura Borges (2017)
The application of air entraining admixture, with controlled proportion, influence mechanical and thermal of concrete. This leads the necessity of studies to evaluate its performance in buildings. The objective of this work is to evaluate the thermal properties of entrapped/entrained air variation concrete (reference - 3%, 8%, 11%, 12%), considering temperatures of brazilian summer period. The methodology includes tests of thermal performance with 16 concretes panels, 4 reference panels and 4 panels for each air incorporated variation, with dimensions of 99 cm × 99 cm × 10 cm, applied at chambers with two isolated thermal compartments; tests with unidirectional heat flux in cylindrical proof bodies (10 cm x 10 cm) extracted from that’s panels and was determined the thermal conductivity in samples (5 cm x 2,5 cm) of the studied concrete according ASTM E1530 – 11. In these tests the thermal performance at the climatized chambers, simulating internal and external conditions, obtained inside temperatures lower than external temperatures to all studied concretes (reference: 8%, 11% and 12%), which is according with the specification of the ABNT NBR 15575: 2013. However, there was no significant difference between the thermal performance of the concretes with incorporated air (8%, 11% and 12%) with the reference concrete (3%), because as the statistical analysis the studied concrete presents the same thermal behavior. The thermal conductivity also resulted in values statistically similar for all studied concretes, but the obtained values was below of specified by standard ABNT NBR 15220: 2005, inclusive the reference concrete. About the thermal transmittance, the studied concretes show values below 3,7 W/m²K, determined according ABNT NBR 15220: 2005, attending, therefore, to the requisites of ABNT NBR 15575:2013 to 3 to 8 climates zones, since that absortância of surface be less than 0,6.